Profit from peer-to-peer. (Economist, 2001)
Part of a special section on technology. Many start-up firms aim to sell peer-to-peer (P2P) computing to larger businesses, but there are risks involved. Such start-ups hope to introduce the P2P style of computing into applications to allow workers to cooperate on joint projects, swap information, and share network resources such as storage space and other costly pieces of equipment. Some critics have rejected P2P as mere hype, stressing issues about security and reliability that continue to be problematic for P2P architecture and the failure of many P2P start-ups. As is the case with many networking ideas, P2P is not a single concept but a wide range of technologies, and it can be defined in several ways. Altogether, it encompasses four separate activities—collaboration among users, interaction among software applications, efficient use of network resources, and supercomputing. The origin of the P2P concept, the fact that it has become synonymous with the controversial Napster file-sharing program, definitions of P2P, efforts to sell P2P services to businesses, and the likely commercial future of P2P are discussed.